2020
DOI: 10.2215/cjn.06780619
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Wide Association Study of CKD

Abstract: Background and objectivesExposure to environmental chemicals has been recognized as one of the possible contributors to CKD. We aimed to identify environmental chemicals that are associated with CKD.Design, setting, participants, & measurements We analyzed the data obtained from a total of 46,748 adults who participated in the National Health and Nutrition Examination Survey (1999–2016). Associations of chemicals measured in urine or blood (n=262) with albuminuria (urine albumin-to-creatinine ratio ≥30 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 61 publications
2
23
0
1
Order By: Relevance
“…Environmental exposures are estimated to account for 70–90% of the risk of acquiring chronic ailments such as diabetes type 2, CKD and cancer [ 271 , 272 ]. The kidney is particularly at risk of injury from long-term use of therapeutic drugs and chronic exposure to environmental toxicants, especially when they are present in the diet [ 273 , 274 , 275 ].…”
Section: Environmental Exposure To CD and Pb Toxic Kidney Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental exposures are estimated to account for 70–90% of the risk of acquiring chronic ailments such as diabetes type 2, CKD and cancer [ 271 , 272 ]. The kidney is particularly at risk of injury from long-term use of therapeutic drugs and chronic exposure to environmental toxicants, especially when they are present in the diet [ 273 , 274 , 275 ].…”
Section: Environmental Exposure To CD and Pb Toxic Kidney Burdenmentioning
confidence: 99%
“…CKD afflicts 8% to 16% of the world population. Diabetes and hypertension are the most common risk factors universally, while obesity is an additional risk factor, especially in industrialized countries [ 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 ]. CKD is a cause of morbidity and mortality as it is an important predictor of end-stage kidney disease (ESKD), stroke and cardiovascular disease (CVD) [ 280 , 281 , 282 , 283 , 284 , 285 ].…”
Section: Environmental Exposure To CD and Pb Toxic Kidney Burdenmentioning
confidence: 99%
“…In particular, early-life exposure to common nephrotoxic Children 2021, 8, 673 2 of 14 elements, such as arsenic (As), cadmium (Cd), and lead (Pb), may disrupt nephrogenesis and primary renal developmental processes that are vital for nutrientwaste homeostasis [3]. As, Cd, and Pb are established nephrotoxicants, pervasive in the environment [4][5][6], with substantial evidence of glomerular or tubular toxicity [7][8][9] as well as nephrotoxic effects in children [10][11][12][13][14][15][16]. However, their joint impact on renal development as a mixture is less well known.…”
Section: Introductionmentioning
confidence: 99%
“…Because early-life exposure to nephrotoxicants may lead to kidney function decline, examining exposure to multiple toxicants individually and as a mixture is increasingly important in the context of real-life exposures. For example, blood Pb and Cd exposure have been individually associated with a reduced estimated glomerular filtration rate (eGFR) and co-exposure to both toxicants increases CKD risk [6,18]. Pb and Cd have also been shown to act non-additively, resulting in worse kidney function decline in adults [6,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that Cd exposure plays a role in the development of chronic kidney disease (CKD) and that Cd can be nephrotoxic at environmental levels [ 5 , 7 ]. A recent exposure-wide association study of over 250 chemicals found that Cd was associated with CKD [ 8 ]. Therefore, identifying preventable risk factors, including environmental exposures in childhood, could contribute to our knowledgebase of early-life intervenable factors for decreasing the incidence of CKD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%